2009
DOI: 10.1248/bpb.32.186
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Induced by a Dihydropyrazine Derivative

Abstract: The Maillard reaction, which comprises a non-enzymatic reaction between reducing sugars and amino acids, produces hundreds of highly reactive compounds. Dihydropyrazine (DHP) is produced by condensation of 2 mol of D-glucosamine, 1) and some DHP derivatives generate various radical species that cause DNA strand cleavage in vitro.2) Since many pyrazine derivatives have been detected in various foods 3) and human urine, 4) we speculated that DHPs, which are presumed to be precursors of pyrazines, would be respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The genotoxic 1,4,29) and cytotoxic 11,28,30) potentials of DHPs have been demonstrated previously. As stated earlier, the biological effects of DHPs are due to DHPs' dual capacity for high chemical reactivity and radical generation activity.…”
Section: +mentioning
confidence: 61%
“…The genotoxic 1,4,29) and cytotoxic 11,28,30) potentials of DHPs have been demonstrated previously. As stated earlier, the biological effects of DHPs are due to DHPs' dual capacity for high chemical reactivity and radical generation activity.…”
Section: +mentioning
confidence: 61%
“…In addition, Cyclohexyl-DHP was shown to possess stronger DNA strand-breaking activity than Me-DHPs and PhDHPs (Maruoka et al, 2005;Yamaguchi et al, 2007). Moreover, we demonstrated that DHPs can potentially generate superoxide anions (Takechi et al, 2009), and not only cause breakage of chromosomal DNA leading to mutagenic lesions but also induce damage to cellular proteins such as glyceraldehyde-3-phosphate dehydrogenase (GAPDH) (Takechi et al, 2010).…”
Section: Introductionmentioning
confidence: 90%
“…11,14) Therefore, we examined and compared the generation of superoxide anions by three DHP derivatives, cyclohexyl-DHP, Me-DHP-1, and Ph-DHP-1, using the highly water-soluble tetrazolium salt WST-1.…”
Section: Generation Of Superoxide Anions and Inhibition Of Gapdh Enzymentioning
confidence: 99%
“…14) In the present study, we examined enzyme inactivation by DHPs using glyceraldehyde-3-phosphate dehydrogenase (GAPDH) as a convenient model protein, since GAPDH is known to be highly sensitive to oxidative damage. 15) Our observations reveal that DHPs inactivate GAPDH in vitro and in vivo.…”
mentioning
confidence: 99%